2020
DOI: 10.3390/ijerph17207499
|View full text |Cite
|
Sign up to set email alerts
|

Group Positive Affect and Beyond: An Integrative Review and Future Research Agenda

Abstract: Group positive affect is defined as homogeneous positive affect among group members that emerges when working together. Considering that previous research has shown a significant relationship between group positive affect and a wide variety of group outcomes (e.g., behaviors, wellbeing, and performance), it is crucial to boost our knowledge about this construct in the work context. The main purpose is to review empirical research, to synthesize the findings and to provide research agenda about group positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 104 publications
(151 reference statements)
1
1
0
1
Order By: Relevance
“…Nurses with high positive affect had higher job performance. The discovery is in line with previous studies (Peñalver et al, 2020 ). The reason is that, on the one hand, emotion is the embodiment of human wisdom and substantially impacts human behaviour, while work is the main activity in people's daily life.…”
Section: Discussionsupporting
confidence: 93%
“…Nurses with high positive affect had higher job performance. The discovery is in line with previous studies (Peñalver et al, 2020 ). The reason is that, on the one hand, emotion is the embodiment of human wisdom and substantially impacts human behaviour, while work is the main activity in people's daily life.…”
Section: Discussionsupporting
confidence: 93%
“…As omnivores have been shown to have fewer positive feelings toward other omnivores than plant‐based eaters have for other plant‐based eaters, 33 this positivity toward other plant‐based eaters may be a protective factor for overall mental health and well‐being. For instance, it has been shown that having shared identities 72 and group positive affect (i.e., positive affect among group members) 73 are associated with resilience and positive emotions. Moreover, although overall mental well‐being and mental health are highly correlated, 66 the reason why we did not observe associations between dietarian identity and depression and anxiety, needs further exploration in a more representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…Teniendo en cuenta los grandes beneficios que aportan los grupos y equipos de trabajo al éxito organizacional (Wilson et al, 2004), no es de extrañar que el estudio del afecto positivo grupal se haya relacionado con una amplia variedad de variables como desempeño grupal, creatividad grupal, eficacia grupal y absentismo (Peñalver et al, 2020). De forma paralela al aspecto individual, a la relación entre el afecto positivo grupal y el desempeño laboral grupal se la bautizó happy-productive group o grupo feliz y productivo (Peñalver, et al, 2019).…”
Section: Grupo Feliz Y Productivo (Happy-productive Group): Hacia Una...unclassified